Implementation of marketing partnerships in industrial enterprises - Мозгова, Галина Валентинівна; Петросян, Т.А. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
This article is devoted to the justification of tools for constructing, maintaining and enhancing strong long-term, mutually beneficial relationships with key partners in the organization of the industrial market: systematic relations strategy, depending on the subjects; proposed recommendations by introducing partnerships; certain organizational and methodological components of the information system implementation and support partnerships.